Faktor Rendahnya Minat Siswa Laki-laki Kelas XII dalam Memilih Jurusan PAUD - Harianti, Putri; Ichsan, Ichsan (Generasi Emas, 2025)
The interest of male students in choosing Early Childhood Education (PAUD) as their major remains relatively low due to various social and cultural factors. This study aims to identify the factors influencing the low interest of 12th-grade male students in Koto Kampar Hulu District Senior High School in selecting PAUD as their major. The research employs a descriptive qualitative method using semi-structured interviews with 15 male students. The findings indicate that the primary factors affecting the low interest of male students include gender stereotypes that perceive the PAUD teaching profession as more suitable for women, social environmental influences from family, peers, and society, as well as the low level of PAUD teachers' welfare, which is considered insufficient for men as the primary breadwinners. This study concludes that strategies are needed to improve PAUD teachers' welfare, change gender perceptions, and provide clearer career pathways for men in the field of early childhood education.